The Hygroscopic Opening of Sesame Fruits Is Induced by a Functionally Graded Pericarp Architecture - Shtein, Ilana; Elbaum, Rivka; Bar-On, Benny (Frontiers in Plant Science, 2016)
To enhance the distribution of their seeds, plants often utilize hygroscopic deformations that actuate dispersal mechanisms. Such movements are based on desiccation-induced shrinkage of tissues in predefined directions. The basic hygroscopic deformations are typically actuated by a bi-layer configuration, in which shrinking of an active tissue layer is resisted by a stiff layer, generating a set of basic movements including bending, coiling, and twisting. In this study, we investigate a new type of functionally graded hygroscopic movement in the fruit (capsule) of sesame (Sesamum indicum L.). Microscopic observations of the capsules showed that the inner stiff endocarp layer is built of a bilayer of transverse (i.e. circumferential) and longitudinal fiber cells with the layers positioned in a semi-circle, one inside the other. The outer mesocarp layer is made of soft parenchyma cells. The thickness of the fibrous layers and of the mesocarp exhibits a graded architecture, with gradual changes in their thickness around the capsule circumference. The cellulose microfibrils in the fiber cell walls are lying parallel to the cell long axis, rendering them stiff. The outer mesocarp layer contracted by 300% as it dried. Removal of this outer layer inhibited the opening movement, indicating that it is the active tissue. A biomechanical hygro-elastic model based on the relative thicknesses of the layers successfully simulated the opening curvature. Our findings suggest that the sesame capsules possess a functionally graded architecture, which promotes a non-uniform double-curvature hygroscopic bending movement. In contrast to other hygroscopic organs described in the literature, the sesame capsule actuating and resisting tissues are not uniform throughout the device, but changing gradually. This newly described mechanism can be exploited in bio-inspired designs of novel actuating platforms.